Strategy for Distributing Zakat Funds to Reduce Poverty in BAZNAS, Tebing Tinggi City - Siregar, Donny Akbar; Syahbudi, Muhammad; Fadhila Rahma, Tri Inda (Management of Zakat and Waqf Journal (MAZAWA), 2025)
This study aims to identify and analyze the zakat distribution strategy implemented by BAZNAS Kota Tebing Tinggi in efforts to reduce poverty. Although the poverty rate in Tebing Tinggi has declined, the number of zakat recipients (mustahik) remains stagnant at approximately 1,000 individuals per year. This stagnation indicates that the zakat utilisation strategy requires a logical measurement ratio and recommendations for improvement. Using a descriptive qualitative approach and the SOAR (Strengths, Opportunities, Aspirations, Results) framework, this research explores perceptions and field data through questionnaires, interviews, and document analysis. The results reveal that Opportunity and Result factors scored highest in supporting the effectiveness of zakat distribution strategies. Opportunities  such  as  policy  support,  zakat  from  professionals,  and  technological advancement are identified as key drivers. Meanwhile, the expected outcomes include the economic independence of mustahik and improved transparency in zakat management. The SOAR approach proves relevant for developing zakat distribution strategies that are not only consumptive but also productive and sustainable